2006
DOI: 10.1097/01.brs.0000232714.72699.8e
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Instrumented Posterior Lumbar Interbody Fusion With One or Two Cages by Finite Element Analysis

Abstract: A single cage inserted in an instrumented PLIF gains approximate biomechanical stability, slight greater subsidence, and a slight increase in screw stress but less early degeneration in adjacent disc. Adjusting these factors, instrumented PLIF with one cage could be encouraged in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 41 publications
1
44
0
2
Order By: Relevance
“…While the maximum stress is still greater, the results for the single cage model do approach those of coupled cages after long-term placement. Chiang et al [3] and Tsuang et al [4] showed that inserting a single oblique cage had a similar immediate effect to coupled cages and drew a conclusion that single-cage PLIF is a useful alternative to traditional two-cage PLIF. Drawing from all results collected in this study, it can be stated that, because the long-term results between the two models are much more similar than the immediate results after implantation, instrumented PLIF with one cage should be further encouraged in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the maximum stress is still greater, the results for the single cage model do approach those of coupled cages after long-term placement. Chiang et al [3] and Tsuang et al [4] showed that inserting a single oblique cage had a similar immediate effect to coupled cages and drew a conclusion that single-cage PLIF is a useful alternative to traditional two-cage PLIF. Drawing from all results collected in this study, it can be stated that, because the long-term results between the two models are much more similar than the immediate results after implantation, instrumented PLIF with one cage should be further encouraged in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this present study did not consider this type of cage placement, but the two placements that were simulated were performed according to the clinical experience and literature [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also reported that range of motion and stress increased when TLIF was done with asymmetrical positioning of a diagonal cage plus unilateral pedicle screw fixation than with symmetrical positioning of the cage during contralateral axial rotation and lateral bending. [4][5][6] Biomechanical weakness and less stability on TLIF itself, unilateral pedicle screw fixation, and asymmetrical positioning of a cage can be causes of postoperative scoliotic change, cage migration, and lower fusion rate of unilateral screw fixation after MIS TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Generally if no neurodefecit, significant number of patients improve with conservative treatment. Its only when this symptoms disable the patient in doing their normal daily routine activities PLIF (surgery) was the final option [11,12,13] . We too in our trial selected patients who underwent conservative treatment and had no improvement and were severely disabled with above symptoms.…”
Section: Discussionmentioning
confidence: 99%